Integrative management of infrastructure and traction equipment at the railway area - N. F. Sirina (Вестник Научно-исследовательского института железнодорожного транспорта, 2020)
Railway transport is in condition of preparation for fulfillment of the forecast increase of transportation. The level of effectiveness and quality of the railways operation is assessed by the period of delivery to the point of destination of required volume of transported freight, which growth increases intensity of infrastructure wear and tear, which requires breaks in trains movement for providing “gaps” for the track repair operations and inevitably results in the delivery time increase.The use of the best speed path of trains is an important component of ensuring energy effectiveness. Transition to the ground process of trains’ movement control allows JSC “RZD” to arrange rhythmic movement of the car traffic movement providing “gaps” in the single opening for the entire ground.Conducted SWOT-analysis determined the risks and potential results of use of the single infrastructure of the railway area in terms of possible additional expenses in the future. Control mechanism of operation costs was proposed, which allows analyzing actual direct expenses and comparing deviations with regard to the set values. Overall algorithm of the model of integrative control of infrastructure and traction resources was formalized, which is illustrated by the example of participants of transportation process at the railway area. The basis of their interaction is the results of integral assessment that generalized various quantity of indicators and assessment factors of transportation process.Mathematical support of procedures of establishing the cost price is implemented in the Intellectual system of control and handling of the locomotive fleet at the area of the railway production infrastructure. Obtained results are integrated in the Automated control system of operation of the single center of infrastructure control and are set for transformation, effective use of the industrial companies potential.Key trends of the geo-economic condition having direct relation to the transportation and logistic operation in Russia determine necessity of effective management of traction resources by means of arrangement of the uniform process of transportation operation of JSC “RZD”, which results in the best use of transportation infrastructure, balanced increase of the volumes of loading and attraction of investments to the railways.